THE IMPORTANCE AND EVOLUTION OF ADULT EDUCATION IN THE 21ST CENTURY (Multidisciplinary Journal of Science and Technology, 2025)
This article explores the evolving landscape of adult education in the 21st century, emphasizing its significance for individuals, economies and societies. It traces the historical development of adult learning and analyzes current forms such as formal, non-formal, and informal education. The paper discusses key challenges including access, digital inequality, and policy gaps, while highlighting the transformative role of technology in adult learning. Finally, the article offers strategic recommendations for making adult education more inclusive, flexible, and future-oriented